Monitoring and Analyzing the Spread of Drug Dealers "Drug Pills Addiction" Using the Geographic Information System (GIS) in Baghdad City for the period 2020 – 2021 - Al-ramahi, Fouad K. Mashee; Zaeen, Ahmed Asaad; Mahmood, Faleh H. x (Iraqi Journal of Science, 2025)
The phenomenon of the drug trade has become a concern for the whole world, due to its negative effects on societies and the frustration that it caused when spreading to all parts of the society after being prevalent among young people only. The purpose of the study is to detect and identify the presence of drug dealers’ gangs and the possibility of their presence and spread according to the neighboring areas and the number of residents. According to the data of the Iraqi Ministry of Interior for the period 2020-2021, organized gangs of the drug trade have become rampant in Iraqi society and are not confined to a specific group or place, but are practiced by many due to the multiple entry and exit outlets for this trade and the lack of control over it. There are many reasons for this organized attack. It was processed using remote sensing techniques and Geographic Information Systems (GIS) ArcMapV10.4 and the use of shapes that simulate reality (shape files) as the study area, which is the city of Baghdad, the capital of Iraq, which was made according to satellite images of the Landsat Satellite, to provide a model to help decision-makers make a set of measures to reduce the spread of the phenomenon of drug trade in Baghdad, confine, and restrict it. The results of the study were that the population had the highest probability of gang spread (1.983-61.52) in the areas of Rashydea, Husseiniya1, Al-Shaab, and Rafydean (Al-Sadr) sub-districts, and the least probability (61.53-189.4) represented the rest of the study areas. The highest probability of spreading the work of drug gangs in relation to the city of Baghdad was (255.52-1,004.3) in Al-Sadr City 1, Al-Sadr City 2, and Rafydean sub-districts. Our study has pioneered in giving results that we believe are the first to be proposed at the level of researchers in the world using modern technologies that simulate reality according to contemporary analysis.